A Thematic Analysis of Weibo Topics (Chinese Twitter Hashtags) Regarding Older Adults During the COVID-19 Outbreak. (3rd September 2020) - Xi, Wanyu; Xu, Wenqian; Zhang, Xin; Ayalon, Liat
Abstract: Objectives: We explored the portrayal of older adults and the public response to topics concerning older adults during the COVID-19 pandemic in Chinese social media (Weibo topics, equivalent to hashtags on Twitter). We also explored the temporal trends of dominant themes to identify changes over time. Methods: Topics related to older adults were searched in the Weibo topic search engine between January 20 and April 28, 2020. Overall, 241 topics and their view frequency and comment frequency were collected. Inductive thematic analysis was conducted to classify the topics into themes. The popularity of each theme was also analyzed. In addition, the frequency with which each theme appeared during the 3 major stages of the pandemic (outbreak, turnover, and post-peak) was reported. Results: Six main themes were identified. "Older adults contributing to the community" was the most prominent theme with the highest average comment frequency per topic. It was also the most dominant theme in the first stage of the pandemic. "Older patients in hospitals" was the second most prominent theme and the most dominant theme in the second and third stages of the pandemic. The percentage of topics with the themes "Care recipients" and "Older adults caring for the young" increased over time. Discussion: The portrayal of older people as being warm, competent, and actively exercising their agency is prevalent on Weibo. The Weibo-viewing public shows signs of interest in intergenerational solidarity during the pandemic in China. These findings are different from findings reported by studies conducted in the West.